Renewable Energy, Internet Penetration, Economic Growth, and Environmental Sustainability Nexus in ASEAN - Azzahrah, Meidiana; Azwardi, Azwardi; Yulianita, Anna (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The study aims to examine the relationship between renewable energy consumption, internet penetration, and economic growth as independent variables, while ecological footprint as dependent variables. The sample of this study uses the ASEAN region, especially Indonesia, Malaysia, Singapore, Thailand, Vietnam, the Philippines, Laos, and Myanmar. These countries were chosen because of their rapid economic growth, large populations, rapid industrialization process, wealth of natural resources, significant foreign investment flows, ongoing economic reforms and more advanced infrastructure developments. Overall, these countries have an important role in the global economy despite still facing a number of challenges. The data used in this study are secondary data available from the World Bank and the Global Footprint Network. The analysis technique used in this study is panel data regression with the period 2011 – 2023. The results of this study found that renewable energy consumption and internet penetration contribute to reducing the ecological footprint in ASEAN while economic growth still contributes to increasing the ecological footprint.